Test information and it using - Andziulienė, Beatričė; Andziulis, Arūnas; Bakanauskaitė, Sonata (Lietuvos matematikos rinkinys, 2002)
The questions of quality of test and test information by using Items Response Theory (IRT) are discussed in this work. Using the IRT gives many chances to make an effective test: to measure not only difficult of everyone test’s item, but what number of information it brings in test; to get an even distribution of items by its difficulty which is harmonize with abilities of testing person; if it’s known how many item gets information in test, it’s possible to make a test which will evaluate the abilities of testing person group best. Analyse of test’s results gives more reversible information for adjustment of education process. Also it lets to diagnose the vacancy of education process: to detect what themes are mastered worst; to find the more difficult items. The reversible information of test lets to recognize the testing persons: to measure the total testing person’s abilities; to detect the vacancies of everyone testing person; to know how everyone of testing person can to work the different type of items. The employing of IRT technologies is correct in different stages of testing process. It helps in objectively evaluating the test quality and increasing efficiency of education process. The estimation of characteristics of tested persons and parameters of test items in the same scale enables to compare the ability of person with the difficult of item. It enables to create the modern potted systems of paperless learning control.